Development of MKID Instrumentation for exoplanet direct imaging - Dodkins, R (2018)
Microwave Kinetic Inductance Detectors (MKIDs) are a highly sensitive cryogenic photodetector. These devices operate by measuring the increase in the surface impedance of a superconducting film when Cooper Pairs are broken by incident photons. This technique allows MKIDs inherent spectral resolution and instantaneous read out with essentially no false counts. In contrast to other cryogenic detectors, the intrinsic multiplexing of the pixels in frequency domain means that arrays of several tens of thousand of pixels can be readout with just a few feed-lines using room temperature radio electronics. These unique properties make MKIDs potentially transformative for exoplanet direct imaging, where residual speckle noise currently limits the minimum mass of the discernible exoplanets to several Jupiter masses. In this thesis I describe some of the developments of MKID instruments required for exoplanet imaging, and I investigate the potential of MKIDs to provide new discoveries in this field. One of the required developments was the automation of the tuning of pixel biasing prior to taking a set of observations. Previously this required inspecting the transmission profile of each pixel by eye and then selecting the optimal power. For the large format arrays necessary for exoplanet direct imaging (on the order of tens of thousand pixels) this process can take approximately 24 human hours to complete. I show that a machine learning-based algorithm can replicate this process in a matter of minutes with equivalent accuracy to that of humans when compared to a control dataset. I then discuss an extension to this algorithm that should enhance the phase measurement performance of MKIDs, ultimately improving the limiting mass of detected exoplanets. Simulation software was developed to make pragmatic predictions on the capabilities of MKIDs for exoplanet direct imaging. This software demonstrates the utility of Dark-Speckle Imaging discrimination technique for a realistic MKID device with appropriate limitations such as maximum count and reduced pixel yield. Possible extensions to this technique that exploit the wavelength dependence of speckles are also explored, which are found to yield superior performance to standard differential imaging methods. I also make predictions on the performance of a next generation MKID-based instrument systems. Preliminary results show that this system can achieve the contrast performance necessary for Neptune sized exoplanets and below. Finally, I present on-sky results of planetary nebula NGC 6751 taken with the ARCONS MKID instrument at Palomar. The inherent spectral resolution of the device meant that a low resolution spectrum of the central star could be created that provided further evidence to clarify its spectral type. The central star was also explored in the time domain at the fine resolution of MKIDs. No periodic feature was found on the time scale of the observation.